Kritik Nalar Al-Jabiri ; Bayani, Irfani dan Burhani dalam Membangun Islamic Studies Integrasi-Interkoneksi - Muhammadun Muhammadun (Eduprof : Islamic Education Journal, 2019)
ABSTRACT The formulation of reasoning in religion, as well as the reformulation of its rationalism, must be based on doctrinal principles, clearly have a specific purpose and purpose, namely aimed at shari'ah makers (Allah and His Messenger) to humans which ultimately lead to human values. wisdom (al-fadilah). The point is that according to al-Jabri, the idea of "maqasid ash-shari'ah" in the religious sciences is comparable to the idea of "the laws of causality in nature" in the discipline of philosophy. Thus, this rearrangement provides a re-foundation of the relationship between babies. and burhani which is based on the rational-empirical paradigm, meaning that the reality of religion and the reality of philosophy is studied in a rational-critical and empirical spirit, with the aim that the experts can preserve the contents of both (religion and philosophy) and reconstruct them again. This is a new direction in the horizon of the knowledge system in the Arab-Islamic world. Abstrak Perumusan penalaran dalam agama, serta reformulasi rasionalismenya, harus berdasar pada prinsip-prinsip doktrinal, secara jelas mempunyai tujuan dan maksud tertentu, yakni ditujukan oleh pembuat syari‟ah (Allah dan Rasul-Nya) kepada manusia yang pada akhirnya membawa manusia kepada nilai-nilai kebijkan (al-fadilah). Intinya menurut al-Jabiri bahwa gagasan “maqasid asy-syari‟ah” dalam disiplin ilmu-ilmu agama sebanding dengan gagasan “hukum-hukum kausalitas di alam ini” dalam disiplin filsafat.Dengan demikian, penataan ulang ini memberikan landasan ulang terhadap hubungan antara bayani dan burhani yang didasarkan pada pradigma rasional-empiris, artinya realitas agama dan realitas filsafat dikaji dengan semangat rasional-kritis dan empiris, hal ini bertujuan agar para pakar dapat menjaga kandungan keduanya (agama dan filsafat) dan merekonstruksinya kembali. Inilah arah baru dalam cakrawala sistem pegetahuan di dunia Arab-Islam.